2018
DOI: 10.3390/app8122581
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Performance Investigation of Nano-TiO2/CaCO3 and Basalt Fiber Composite Modified Asphalt Mixture under Freeze‒Thaw Cycles

Abstract: The objective of this research is to evaluate the pavement performance degradation of nano-TiO 2 /CaCO 3 and basalt fiber composite modified asphalt mixtures under freeze-thaw cycles. The freeze-thaw resistance of composite modified asphalt mixture was studied by measuring the mesoscopic void volume, stability, indirect tensile stiffness modulus, splitting strength, uniaxial compression static, and dynamic creep rate. The equal-pitch gray prediction model GM (1,3) was also established to predict the pavement p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The nano-TiO 2 /CaCO 3 was developed and provided by the college of chemistry, Jilin University [ 41 ]. Its detailed technical characteristics are presented in Table 2 .…”
Section: Raw Materials and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nano-TiO 2 /CaCO 3 was developed and provided by the college of chemistry, Jilin University [ 41 ]. Its detailed technical characteristics are presented in Table 2 .…”
Section: Raw Materials and Experimental Methodsmentioning
confidence: 99%
“…Prior studies that have noted the reasonable dosage of nano-TiO 2 /CaCO 3 is 5% in weight of bitumen [ 41 ]. During the preparatory stage of nano-TiO 2 /CaCO 3 modified bitumen, original bituminous material was preheated to 160 °C and next it was blended with modified nano-TiO 2 /CaCO 3 by manually stirring for 5 min.…”
Section: Raw Materials and Experimental Methodsmentioning
confidence: 99%
“…At the third stage of research, the interaction of basalt fiber with etching solutions is studied in order to adjust the chemical composition in the direction of obtaining the maximum content of silica, aluminum, and titanium. The choice of an acid solution and the establishment of optimal values of their characteristics is based on an analysis of the properties of the constituent parts of the basalt fiber material [18]. The concentration of the etching solution is 3.25 and the temperature of the solution is 50 °C, the exposure time is 60-65 minutes.…”
Section: Fig 7 the Placement Of Active Zones On The Surface Of Basamentioning
confidence: 99%
“…The results indicated that the multi-axial strength decayed significantly after 20 freeze-thaw cycles [17]. Wang et al conducted a freeze-thaw split to evaluate the flexural resistance damage caused by freeze-thaw cycles [6,15,18,19,20].…”
Section: Introductionmentioning
confidence: 99%